INPP4B exerts a dual function in the stemness of colorectal cancer stem-like cells through regulating Sox2 and Nanog expression. (8th June 2019) - Yang, Liwen; Ding, Chenbo; Tang, Wendong; Yang, Taoyu; Liu, Min; Wu, Hailu; Wen, Kunming; Yao, Xinsheng; Feng, Jihong; Luo, Junmin
Abstract: Inositol polyphosphate 4-phosphatase type II (INPP4B), a lipid phosphatase, was identified as a negative regulator of phosphatidylinositol 3-kinase (PI3K)/Akt signaling in several cancers. The expression and biological function of INPP4B in human colorectal cancer (CRC) are controversial, while the role and molecular mechanism of INPP4B in colorectal cancer stem-like cells (CR-CSLCs) remains unclear. Here, we observed that INPP4B expression was markedly decreased in primary non-metastatic CR-CSLCs and increased in highly metastatic CR-CSLCs compared with corresponding control non-CSLCs. INPP4B overexpression inhibited self-renewal, and chemoresistance of primary non-metastatic CR-CSLCs, but exerted the opposite roles in highly metastatic CR-CSLCs in vitro . Similarly, INPP4B knockdown had dual functions in the self-renewal and chemoresistance of different CR-CSLCs. In addition, we demonstrated that INPP4B overexpression suppressed the tumorigenicity of primary non-metastatic CR-CSLCs while induced the tumorigenicity of highly metastatic CR-CSLCs in nude mice. Furthermore, INPP4B was found to modulate the stemness of CR-CSLCs by regulating Sox2 and Nanog expression, which was dependent on PI3K/PTEN/Akt signaling. In conclusion, our results highlight an important role of INPP4B in the stemness of CR-CSLCs for the first time and emphasize INPP4B as a dual therapeutic target for suppressing primary cancer cell proliferation and for preventing metastasis in CRC patients. Abstract : The present study suggests that INPP4B plays a dual role in stemness of CR-CSLCs, and emphasize INPP4B as a dual therapeutic target for depressing primary cancer cell growth and for preventing metastasis in CRC patients.